MAGNESIUM SULFAT DALAM TATALAKSANA TETANUS GENERALISATA: SEBUAH LAPORAN KASUS DAN TINJAUAN LITERATUR SINGKAT - Danerdi, I Made Adhi Kresnayana (PERDOSNI, 2025)
Background: Tetanus is a life-threatening neurologic disorder characterized by muscle spasms, hypertonia, and autonomic dysfunction. Magnesium sulphate is a widely available medication that can inhibit catecholamine release and antagonize calcium action in cardiomyocytes and neuromuscular junctions. Thus, this agent could be used as an adjuvant treatment to control spasms and prevent dysautonomic dysfunction in tetanus. However, the use of this medication in tetanus is still rare because of concerns about the adverse effects of muscle paralysis. Case Report: A 48-year-old male patient presented with trismus, neck stiffness, dysphagia, and abdominal rigidity a few days after poking his caries teeth with a nail clipper. There is no history of seizure, fever, trauma, or surgery. He was conscious, hemodynamically stable, and had normothermia. Thus, he was diagnosed with generalized tetanus and was treated with human tetanus immunoglobulin, antibiotics, sedatives, anticonvulsants, and analgetic. Magnesium sulphate infusion was also given since the first day of admission and maintained until seven days of hospitalization. During the first week of treatment, he was hemodynamically stable and clinically improved. On day 14, trismus and dysphagia significantly improved, while abdominal rigidity and neck stiffness were absent. The patient was then discharged. Conclusion: Timely diagnosis and management were vital to preventing mortality in tetanus. Despite concerns about the adverse effects of magnesium sulphate, this case report proved that magnesium sulphate is safe and effective in reducing muscle spasms and preventing autonomic dysfunction in tetanus patients. Keywords: Magnesium sulphate, MgSO4, Tetanus, Spasms